CLA GAME REPORT : Causal Layered Analysis Game on Neo-Carbon Energy Scenarios - Heinonen, Sirkka; Balcom Raleigh, Nicolas; Karjalainen, Joni; Minkkinen, Matti; Parkkinen, Marjukka; Ruotsalainen, Juho (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku, Turku School of Economics|, 2019)
This report describes the process and results of Causal Layered Analysis (CLA) game session held on 11 June 2015 in the International Conference of “Futures Studies Tackling Wicked Problems”, organized by Finland Futures Research Centre in Turku. CLA is a qualitative method developed by Sohail Inayatullah. It enables a deeper investigation of alternative futures through an analysis done through four different layers; litany, system, worldview and myth/metaphor. The method functioned as the theoretical framework for the experimental game session conducted during the conference. The aim of the CLA game was to elaborate on and experiment with four transformational scenarios being developed by Finland Futures Research Centre for an ongoing Neo-Carbon Energy project. The tentative scenarios were constructed in the futures-orientated part of the project “Neo-Carbon Enabling Neo-Growth Society – Transformative Scenarios 2050”.